Preparation and Properties of Nano Diamond/6F-Bisphenol A-Based Cyanate Ester Composites - KAHRAMAN, MEMET VEZİR (WILEY, 2013)
The aim of this study was to improve thermal conductivity, thermal stability, and mechanical properties of bisphenol A dicyanate ester (BADCy) by adding bisphenol A dicyanate ester containing fluorine (F-BADCy) and nano diamond. The cyanate esters containing fluorine/nano diamond composites having various ratios of BADCy, F-BADCy, and nano diamond were prepared. Thermal stability and thermal conductivity of the samples were evaluated by thermogravimetric analysis, differential scanning calorimetry and laser flash method, respectively. The samples were characterized with the following analysis; gel content, water absorption capacity, and stress-strain test. Hydrophobicity of the samples was determined by the contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy (SEM). The obtained results prove that the cyanate ester containing fluorine/nano diamond composites have good thermal and mechanical properties and they can be used in many applications such as electronic devices, materials engineering, and other emergent. POLYM. COMPOS., 34:1977-1985, 2013. (c) 2013 Society of Plastics Engineers
Keywords: THERMAL-PROPERTIES; NANODIAMOND; NANOCOMPOSITES